Gabby & Grandma Go Green - Wellington, Monica (New York : Dutton Children's Books, 2011)
Gabby and her grandmother spend the day together doing things that help the environment, from sewing cloth bags out of fabric scraps to dropping off their recycling and visiting the library for more helpful ideas.
Keywords: Environmental protection -- Fiction; Grandmothers -- Fiction